2021
DOI: 10.33483/jfpau.989733
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies on Some 4,5-Dihydro-1h-Pyrazole Derivatives as Cyclooxygenase Inhibitors

Abstract: Objective: To examine the interactions of some 4,5-dihydro-1H-pyrazole derivatives, which are thought to have antiinflammatory effects, with cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) enzymes, docking studies were carried out on these enzymes.Material and Method: COX-1 enzyme (3KK6) and COX-2 enzyme (3LN1) were selected from the protein data bank for docking studies. The ligand and protein constructs were prepared using Autodock 1.5.6. AutoDock Vina was used to determining the binding affinity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The interactions shown by Eupatilin was discovered to be analogous to the interaction induced by celecoxib in the active site of COX-2. 42 Thus, it was suggested that, Eupatilin was proposed to interact with COX-2 in a manner similar to celecoxib by binding to the same active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions shown by Eupatilin was discovered to be analogous to the interaction induced by celecoxib in the active site of COX-2. 42 Thus, it was suggested that, Eupatilin was proposed to interact with COX-2 in a manner similar to celecoxib by binding to the same active site.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions shown by Eupatilin was discovered to be analogous to the interaction induced by celecoxib in the active site of COX-2. 42 Thus, it was suggested that, Eupatilin was proposed to interact with COX-2 in a manner similar to celecoxib by binding to the same active site. Moreover, it would be prudent to assess the efficacy of Eupatilin on a genetically induced arthritis model in addition to the CFA-induced arthritis model, since the former somewhat resembles RA and serves as the study's primary limitation.…”
Section: Discussionmentioning
confidence: 99%